'Don't forget the children' – test before it is too late. (February 2017) - Malik, S; White, V; Sundaram, S; Humphreys, K; Patel, R; Samraj, S
In 2009, 'Don't forget the children' guideline recommended that all new HIV-positive patients attending adult HIV services should have any existing children identified and tested for HIV alongside a coherent documentation process. A retrospective case note review was performed on 173 HIV-positive women registered at the Royal South Hants adult HIV service until 31 January 2014. Data were assessed as a whole (n = 173) and, in addition, two comparator groups were formulated: (a) pre-guidelines (n = 108) and (b) post-guidelines (n = 65). Out of 80 children eligible for HIV testing, only 43 (54%) had clear documentation of a test result, and in the remaining 37 (46%), it was either not considered or not followed through. Documentation of need for testing increased significantly from 67% in pre-guideline group to 100% in the post-guideline group (p < 0.001). The median time from recognition of need to test to actual testing remained 24 months in both groups. Although this audit demonstrated improvement in identification of at-risk children and their testing, there is still need for improvement.